Happiness Factors and Indicators of Public Health Staff Operation Working in Health Promoting Hospital, Yala Provinces - Saiwaree, Montira; Nawsuwan, Kittiporn; Sukhonthachit, Penmat (Princess of Naradhiwas University Journal, 2021)
This quantitative research aims to study happiness factors and indicators of public health staff operation working in Health Promoting Hospital located in Yala provinces. 300 sampling of staff who are working in Health Promoting Hospital located in Yala provinces and collected by self – administered questionnaires as a research tool. Descriptive statistics were used to describe general characteristics of public health staff with percentage, and analyze factor with exploratory factor analysis (EFA). The results showed that happiness factors and indicators of public health staff operation working in Health Promoting Hospital consisted of 8 factor and 47 indicators including 1) the 1st factor is relationship among people having 10 indicators, 2) the 2nd factor is positive thinking having 7 indicators, 3) the 3rd factor is life satisfaction having 7 indicators, 4) the 4th factor is recognition and reliability having 6 indicators, 5) the 5th factor is work satisfactory having 6 indicators, 6) the 6th factor is leader satisfactory having 4 indicators, 7) the 7th factor is work happiness having 4 indicators, 8) the 8th factor is family relationship having 3 indicators. The results revealed that all indicators are accurate according to the actual condition a statistically significant at 0.05 (p-value < 0.001). The results could be developed as happiness investigation tool and encouraged public health staff operation working in Health Promoting Hospital located in Yala province.